2012
DOI: 10.1186/1472-6882-12-172
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life, immunomodulation and safety of adjuvant mistletoe treatment in patients with gastric carcinoma – a randomized, controlled pilot study

Abstract: BackgroundMistletoe (Viscum album L.) extracts are widely used in complementary cancer therapy. Aim of this study was to evaluate safety and efficacy of a standardized mistletoe extract (abnobaVISCUM® Quercus, aVQ) in patients with gastric cancer.Patients and Methods32 operated gastric cancer patients (stage Ib or II) who were waiting for oral chemotherapy with the 5-FU prodrug doxifluridine were randomized 1:1 to receive additional therapy with aVQ or no additional therapy. aVQ was injected subcutaneously thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
47
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 25 publications
1
47
0
3
Order By: Relevance
“…Similarly, combining Iscador with carboplatin for advanced non‐small‐cell lung cancer can allow lower effective doses of otherwise toxic chemotherapy agents and reduce deleterious side effects (Bar‐Sela et al ., ). Similar findings are reported around the world, where standardized mistletoe extract (abnoba VISCUM(®) Quercus, aVQ) in patients with gastric cancer used with 5‐FU prodrug doxifluridine can with improved quality of life (Brandenberger et al ., ; Kim et al ., ) and reduce chemotherapy side effects (Eisenbraun et al ., ). Summative analysis of clinical oncology trials using mistletoe therapy consistently report adjunct use as safe with ability to improve quality of life (Melzer et al ., ) and overall survival (Ostermann et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, combining Iscador with carboplatin for advanced non‐small‐cell lung cancer can allow lower effective doses of otherwise toxic chemotherapy agents and reduce deleterious side effects (Bar‐Sela et al ., ). Similar findings are reported around the world, where standardized mistletoe extract (abnoba VISCUM(®) Quercus, aVQ) in patients with gastric cancer used with 5‐FU prodrug doxifluridine can with improved quality of life (Brandenberger et al ., ; Kim et al ., ) and reduce chemotherapy side effects (Eisenbraun et al ., ). Summative analysis of clinical oncology trials using mistletoe therapy consistently report adjunct use as safe with ability to improve quality of life (Melzer et al ., ) and overall survival (Ostermann et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Our data reveals that total white blood cell counts were not significantly changed, but monocyte counts were slightly decreased after SB administration. However, one of the other well-known natural anticancer drug studies using mistletoe reported that total white blood cell and monocyte counts were increased, probably due to its immunogenic lectin component [12]. Disrupted CD4 T cell percentages were normalized 10 days after the SB administration, and decreased cell counts were moderately increased to the normal level seen within the healthy Korean population [13].…”
Section: Discussionmentioning
confidence: 97%
“…Currently, the spectrum of published mistletoe QOL-oriented research is limited to studies assessing general well-being improvement (Brandenberger et al [2012]; Eisenbraun et al [2011]; Kienle & Kiene [2010]; Semiglazov et al [2006]; Piao et al [2004]). Studies on specific symptom improvement include leukopenia and diarrhea in gastric cancer patients (Kim et al [2012]), reducing malignant ascites (Bar-Sela et al [2006]), improving emotional concerns in palliative care (Heusser et al [2006]), and lessening of nausea/vomiting in breast cancer patients receiving adjuvant chemotherapy (Loewe-Mesch et al [2008]). Most importantly, mistletoe safety aspects have also been studied and complement the emerging data on efficacy (Kienle et al [2011]; Augustin et al [2005]).…”
Section: Discussionmentioning
confidence: 99%